Simple, Immediate and Calibration-Free Cyclotron Proton Beam Energy Determination Using Commercial Targets - Sergio J.C. do Carmo (Instruments, 2019)
This work presents a simple method for determining the energy of the proton beam in biomedical cyclotrons, using no additional experimental set-up and only materials from radioisotope routine productions that are therefore available on-site. The developed method requires neither absolute efficiency calibration nor beam current measurements, thus avoiding two major sources of uncertainty. Two stacks composed of natural titanium thin foils, separated by an energy degrader of niobium, were mounted in a commercial target and irradiated. The resulting activities of 48V were assessed by a HPGe spectrometer.